Deteksi Hiperkolesterolemia pada Masyarakat Kota Siak Sri Inderapura - Ismawati Ismawati; Imelda Tresia Pardede (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Coronary heart disease (CHD) is a disorder caused by the process of atherosclerosis in the coronary arteries which results in disruption of blood flow to the heart muscle. Various attempts have been made to control CHD but have not given optimal results. One of the basic steps in controlling is to do a health screening that is checking blood cholesterol. The purpose of this service activity is to improve the control of CHD risk factors by detecting hypercholesterolemia so that it is expected to reduce the incidence of CHD. The program was carried out in collaboration with Siak District Hospital and Siak branch IDI. Prospective service participants register online and fill in data in the form of the name, gender, age, address, occupation, height, and weight. On the day of the activity, participants were re-registered. Next is a blood cholesterol check and education about hypercholesterolemia and its management. The effort to detect hypercholesterolemia and education in the Sri Inderapura Siak City community was carried out in August 2019 at the Tengku Maharatu Building. Measurement of community cholesterol levels is done by using a digital inspection tool. On examination found that most participants had normal total cholesterol levels which were 55.94%, while hypercholesterolemia was found in 26 participants (44.06%).